E-COMMERCE AND E-CONTRACTS: CHALLENGES, RISKS AND OPPORTUNITES IN THE CROSS-BORDER MARKETS - Artur GOLBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The popularity of e-commerce is growing more and more, being widely accepted and promoted by both consumers and businesses. The scientific investigation has the purpose to study the commercial relations which take place in the virtual environment, where people buy and sell products and services, using more and more e-contracts and e-commerce platforms. In this scientific research are analyzed types and advantages of e-commerce, the categories of e-contracts, the consent and the validity of e-contracts, the legal framework of the Republic of Moldova in the area of study and the risks related to them and the opportunities in the cross-border markets. In the research was used statistical data from the National Bank of Moldova, the National Bureau of Statistics of the Republic of Moldova and other sources. The main conclusion of the scientific analysis is that electronic contracts have a high importance in the development of the cross border markets but they generate risks which need to be managed. The main results of the scientific paper consist of the highlighting the necessity of additional algorithms, questions before signing the electronic contracts in order to reduce the risks and to be more protected.